The use of participatory video in adaptation to environmental change : a case study in Wage Worgaja, Ethiopia - Castro, Luis Miguel (Department of Environmental and Geographical Science, 2014)
Changes in the environment require a range of responses and adaptations at different levels. One of the levels where adaptation is needed is at the community level in developing countries. This research evaluated the effectiveness of participatory video when used to articulate and communicate messages of adaptation to environmental change.